Quality evaluation of health foods containing licorice in the Japanese Market. (2019) - Ishimi, Y; Takebayashi, J; Tousen, Y; Yamauchi, J; Fuchino, H; Kawano, T; Inui, T; Yoshimatsu, K; Kawahara, N
Graphical abstract: Highlights: The contents of glabridin and medical component glycyrrhizin were analyzed in herbal medicines and health foods containing licorice. A small amount of glycyrrhizin was detected in some of health foods. Estrogenic activity was detected in some of health food ingredients and health foods. Antioxidant activity was detected in all the materials. Assessment of hepatic CYP activity, liver and uterine weights in estrogen deficient mice was useful for evaluating the safety of estrogenic ingredients. Abstract: Focusing on licorice, a highly used raw material in health foods, quantitative analysis of functional/medicinal components and a safety and functional evaluation was carried out for herbal medicines, health food ingredients, and so-called health foods. A functional component, glabridin, was detected in herbal medicines from Glycyrrhiza glabra and G. inflata, health food ingredients, and in commercially available health foods that contain licorice. Likewise, glycyrrhizin, a medicinal component, was detected in these sources, except in licorice oil extract. Estrogen activity in vitro was detected in some of the herbal medicines, health food ingredients, and in health foods containing licorice. In the in vivo study, liver weight in ovariectomized (OVX) mice treated with licorice oil extract was significantly higher than that in OVX and sham mice in a dose dependent manner. These results suggest that excessive intake of licorice oil extract from health foods should be avoided, even though these ingredients might be beneficial for medical use in order to maintain bone health in postmenopausal women. Measurement of hepatic cytochrome P-450 (CYP) activity, reproductive organ weight, and fat and bone mass in OVX mice was considered useful for evaluating the safety and efficacy of estrogenic health food ingredients derived from herbal medicines.